The Implementation of Write-Around Strategy to Enhance Students’ Descriptive Writing Skills - Iwan Dudy Gunawan; Wahilda Ikhsan Perdana (SALEE: Study of Applied Linguistics and English Education, 2025)
This classroom action research aimed to explore the implementation of the Write-around strategy to improve students' descriptive writing skills in an Indonesian EFL classroom. Conducted over two cycles involving 32 seventh-grade students at Junior High School 29 Bandung, the study examined how collaborative writing activities affect students' writing performance and engagement. Data were collected through observations, pre- and post-tests, questionnaires, and field notes. Findings indicated a significant improvement in students’ writing scores, with the average increasing from 59.6 to 75.9. Students demonstrated better control of grammar, vocabulary, and mechanics, as well as improved confidence and understanding of text structure. Questionnaire results revealed that most students found writing more enjoyable and less intimidating when working with peers. The Write-around strategy encouraged active participation, peer feedback, and the co-construction of ideas, aligning with previous research that highlights the benefits of cooperative learning. Despite minor challenges in idea sequencing during group writing, the strategy proved to be an effective method for supporting both cognitive and affective aspects of language learning. It is recommended that teachers adopt collaborative strategies like Write-around to foster a more interactive and supportive environment for developing writing skills in EFL contexts.